2020
DOI: 10.1007/s00192-020-04609-6
|View full text |Cite
|
Sign up to set email alerts
|

Suturing methods in prolapse surgery: a biomechanical analysis

Abstract: Introduction Pelvic organ prolapse is a common problem in urogynecological surgery. Abdominal and laparoscopic sacrocolpopexy is currently considered to be the gold standard of treatment. The main problem remains the anatomical point of fixation as well as how sutures are placed. We evaluated the biomechanical difference between an in-line ligament suture versus an orthogonal ligament suture and a single suture versus a continuous suture at the anterior longitudinal ligament in an in-vitro, sacro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Comparing those data, there was a slight difference, but the data remain at the same order of magnitude. The same applies to the parameter displacement at failure which was 16 ± 2 mm in group 4 and 29 ± 6 mm for human tissue ( p = 0.0005) and the recorded parameter stiffness with values of 5.31 ± 0.97 mm/N for porcine tissue and 2.99 ± 0.86 mm/N for human fiber [ 18 ] ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Comparing those data, there was a slight difference, but the data remain at the same order of magnitude. The same applies to the parameter displacement at failure which was 16 ± 2 mm in group 4 and 29 ± 6 mm for human tissue ( p = 0.0005) and the recorded parameter stiffness with values of 5.31 ± 0.97 mm/N for porcine tissue and 2.99 ± 0.86 mm/N for human fiber [ 18 ] ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 79%
“…The second study, also conducted by Sauerwald et al [ 20 ] examined the time until functional stability in pectopexy by means of cyclic testing and detected that functional stability is achieved after 19.1 cycles of a load exposure of below 25 N. Therefore, patients do not have to fear a global fixation failure. The third biomechanical analysis found in the current literature performed by Hachenberg et al [ 18 ] is already mentioned above. This study, performed on human cadaver pelvices, showed that an orthogonally placed suture is superior to an in-line suture at the sacrospinal ligament.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations